Developmental transcriptomics in Pristionchus reveals the environmental responsiveness of a plasticity gene-regulatory network - Reich, Shelley; Loschko, Tobias; Jung, Julie; Nestel, Samantha; Sommer, Ralf J.; Werner, Michael S. (Genome Research, 2025)
Developmental plasticity enables the production of alternative phenotypes in response to different environmental conditions. Although significant advances in understanding the ecological and evolutionary implications of plasticity have been made, understanding its genetic basis has lagged. However, a decade of genetic screens in the model nematode Pristionchus pacificus has culminated in the identification of more than 30 genes that affect mouth form. We also recently reported the critical window of environmental sensitivity and therefore have clear expectations for when differential gene expression should matter. Here, we collated existing data into a gene-regulatory network (GRN) and performed developmental transcriptomics across different environmental conditions, genetic backgrounds, and mutants to assess the regulatory logic of mouth-form plasticity. We find that only two genes in the GRN (eud-1 and seud-1/sult-1) are sensitive to the environment during the critical window. The time points of their sensitivity differ, suggesting that they act as sequential checkpoints. Additionally, seud-1/sult-1 is differentially expressed across strains and species with different mouth-form biases, highlighting the potential role of switch-gene regulation in the evolution of plasticity. We also observe temporal constraint upon the transcriptional effects of mutating the GRN and reveal unexpected feedback between mouth-form genes. Finally, a comprehensive analysis of all samples identifies metabolism as a shared pathway for regulating mouth-form plasticity. These data are presented in a Shiny app to facilitate gene expression comparisons across development in up to 14 different conditions. Collectively, our results divide the GRN for mouth-form plasticity into environmentally sensitive switch genes and downstream genes that execute the decision.
10.1101/gr.279783.124